2019
DOI: 10.3390/jcm9010017
|View full text |Cite
|
Sign up to set email alerts
|

Histological Scores Validate the Accuracy of Hepatic Iron Load Measured by Signal Intensity Ratio and R2* Relaxometry MRI in Dialysis Patients

Abstract: Almost all haemodialysis patients are treated with parenteral iron to compensate for blood loss and to allow the full therapeutic effect of erythropoiesis-stimulating agents. Iron overload is an increasingly recognised clinical situation diagnosed by quantitative magnetic resonance imaging (MRI). MRI methods have not been fully validated in dialysis patients. We compared Deugnier's and Turlin's histological scoring of iron overload and Scheuer's classification (with Perls' stain) with three quantitative MRI me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…Since not all our patients had saved individual eight echoes in the clinic scans for calculating the offline classic R2* results by using the magnitude-based monoexponential model 6 , we used the scanner-generated the complex-based IDEAL-IQ R2* results. A newly published study 13 found the classic R2* and IDEAL-IQ R2* were significantly correlated to each other (r = 0.9231, p < 0.0001), and the patient R2* range covered our patients R2*.…”
Section: Objectivessupporting
confidence: 59%
“…Since not all our patients had saved individual eight echoes in the clinic scans for calculating the offline classic R2* results by using the magnitude-based monoexponential model 6 , we used the scanner-generated the complex-based IDEAL-IQ R2* results. A newly published study 13 found the classic R2* and IDEAL-IQ R2* were significantly correlated to each other (r = 0.9231, p < 0.0001), and the patient R2* range covered our patients R2*.…”
Section: Objectivessupporting
confidence: 59%
“…Liver iron concentration (LIC) was measured in this patient on 13th August, 2019 by quantitative magnetic resonance imaging (qMRI) comprising three simultaneous methods: Signal Intensity Ratio (SIR) according to Rennes University, classical R2* relaxometry, and R2* relaxometry with multi-peak fat spectral modeling (R2*-IDEAL-IQ relaxometry) [ 3 ]. The Garbowski equation was used in R2* relaxometry (classical and IDEAL-IQ) to translate hepatic T2* expressed in ms into µmol/g dry liver [ 4 ].…”
Section: Casementioning
confidence: 99%
“…Splenic iron concentration (SIC) was also assessed during the same session by R2* relaxometry [ 3 ] and SIC concentration was extrapolated in µmol/g using the Garbowski equation [ 4 ].…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…The liver is the main site of iron storage, and liver iron concentration is a valuable marker of total body iron stores, which can be measured noninvasively and accurately by quantitative magnetic resonance imaging in iron overload disorders including dialysis patients. 95 , 96 Recent studies of liver iron stores in dialysis patients by quantitative magnetic resonance imaging and susceptometry have revealed a high frequency of radiologic hemosiderosis (affecting up to 66% of the 500 dialysis patients in a pooled analysis of 11 published radiologic studies on liver iron concentration), therefore questioning the potential hazards of routine indiscriminate administration of high-dose IV iron in this setting. 97 , 98 …”
Section: Anemia—a Major Complication Of Ckdmentioning
confidence: 99%